1991
DOI: 10.3102/00028312028003643
|View full text |Cite
|
Sign up to set email alerts
|

Interest and Learning From Text

Abstract: Dewey (1913) suggested some time ago that trying to find out what is of interest to students is an important part of schooling; on the other hand, “making things interesting” is artificial and often unsuccessful. Two studies investigating the placement of interesting detail in a text about a physicist and his scientific work are reported here. In both studies, undergraduate students were asked to read the science text under a variety of conditions and then to recall important information on a set of measures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
78
3
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(90 citation statements)
references
References 13 publications
4
78
3
1
Order By: Relevance
“…The present findings suggest as well that interest in a text can be manipulated externally (Deci, 1992;Garner et al, 1991;Hidi et al, 1992). One explanation for this finding is that text segments become more interesting when they are central to an activated schema (Renninger, 1992).…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The present findings suggest as well that interest in a text can be manipulated externally (Deci, 1992;Garner et al, 1991;Hidi et al, 1992). One explanation for this finding is that text segments become more interesting when they are central to an activated schema (Renninger, 1992).…”
Section: Resultsmentioning
confidence: 68%
“…These questions are important because previous research has manipulated interest by using different texts or altering information within a single text rather than changing the way readers study a single text (Baldwin, Peleg-Bruckner, & McClintock, 1985;Garner et al, 1991;Hidi & Baird, 1988). Presently, it is unclear whether interest in a particular text is due to the content of the text, the context in which that information is encountered, or both.…”
mentioning
confidence: 96%
“…Hence, the user's processing capacity may be lower for uninteresting posts as compared with postings the user finds interesting. In fact, prior research on interestingness of text has shown that individuals recall uninteresting texts less frequently as compared with interesting ones when faced with large amounts of data (Garner et al, 1991). …”
Section: Behavior Of Osn Contacts and Trustmentioning
confidence: 97%
“…Studies found that readers' background knowledge about the texts can influence text interpretation (Garner, Alexander, Gillingham, Kulikowich, & Brown, 1991). That is, when teacher education students with insufficient teaching experiences read ideological education news, they may perceive a gloomy picture for education and further decrease their enthusiasm for education jobs.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%